Analisis SWOT dalam Pengembangan PPSDM Aparatur Menuju Corporate University - Maliani, Ani (Pusat Pengembangan Sumber Daya Manusia Aparatur, 2021)
ABSTRACTIncreasing quality of human resources development continues to be demanded to contribute to the existence of an organization, as well as the PPSDM Aparatur which has the goal of being able to become an institutional entity as a corporate university in 2023 according to existing regulations. The aim of the research was to take the figure to what extent the PPSDM Aparatur fulfilled the components needed for the establishment of the corporate university. SWOT analysis method is conducted to find what strategic direction is needed in fulfilling those components above, which used questioner from PPSDM Aparatur employee. The result the IFAS value is 1.35 and EFAS 1.7. These two components direct the position of large organizations in quadrant I. This benefits the organization because it shows that PPSDM is strong enough and has the opportunity to lead to aggressive policies. The results of the post-education and training evaluation in 2019, which are the parameters used for training at PPSDMA as a comparison with the SWOT results show several improvements that need to be improved, such as a review of operational procedure standard training policy from planning until evaluation program. This result shows that the SWOT analysis is used as the first step in managing the strategic direction of PPSDM Aparatur towards the corporate university. However, it needs expert judgment to assess and direct the fulfillment of the company's components. so writers made of conceptual model and road map the PPSDM Aparatur corporate university in 2023 can be achieved. ABSTRAKPeningkatan mutu pengembangan sumberdaya manusia terus dituntut dalam upaya turut berkontribusi terhadap eksistensi suatu organisasi, begitupun PPSDM Aparatur yang memiliki cita-cita pada tahun 2023 mampu menyusun suatu entitas lembaga sebagai corporate university sesuai amanah peraturan yang berlaku. Penelitian ini bertujuan memotret sejauh mana PPSDM Aparatur memenuhi komponen-komponen yang diperlukan untuk berdirinya corporate university tersebut. Metode yang dilakukan berupa Analisis SWOT untuk melihat arah strategi apa yang dibutuhkan dalam pemenuhan komponen di atas dengan menggunakan kuesioner kepada para pegawai PPSDM Aparatur. Hasilnya menunjukan nilai IFAS 1.35 dan EFAS 1.7. Kedua komponen ini mengarahkan posisi grand strategi organisasi ada di kuadran I. Hal ini menguntungkan organisasi karena menunjukan bahwa PPSDM Aparatur cukup kuat dan memiliki peluang sehingga melahirkan kebijakan agresif. Disatu sisi hasil evaluasi paska diklat pelatihan tahun 2019 di PPSDM Aparatur yang dijadikan pembanding hasil analisis SWOT menunjukkan beberapa perbaikan yang perlu dilakukan, seperti review SOP kebijakan kediklatan perencanaan hingga evaluasi. Hal ini menunjukkan bahwa SWOT dapat digunakan sebagai langkah awal dalam mengenali arah strategi PPSDM Aparatur menuju corporate university, namun berikutnya perlu expert judgement yang menilai dan mengarahkan pemenuhan komponen-komponen tersebut seperti yang disusun penulis melalui rancangan model dan road map PPSDM Aparatur Corporate university sehingga pada tahun 2023 dapat tercapai.